'Make Them Wonder How You Are Still Smiling': The Lived Experience of Coping With a Brain Tumour. (June 2023) - Zanotto, Anna; Goodall, Karen; Ellison, Marion; McVittie, Chris
A brain tumour can be a life-threatening illness and cause unique symptoms compared to other types of cancer, such as cognitive or language deficits, or changes in personality. It is an exceptionally distressing diagnosis which can affect quality of life, even for those with a low-grade tumour or many years after the diagnosis. This study sought to gain an in-depth understanding of the lived experience of adjustment to living with a brain tumour. Twelve individuals (83% female) with a primary brain tumour (83% low-grade) took part in the study. Participants were aged 29–54 years, on average 43 months following the diagnosis, and were recruited through the charitable support organisations in the United Kingdom. In-depth semi-structured interviews were conducted, transcribed verbatim, and analysed using interpretative phenomenological analysis (IPA). Six inter-related themes were identified: making sense of the diagnosis, seeking empowerment, feeling appreciative, taking charge of coping, learning to accept, and negotiating a new normality. Notions of empowerment, gratitude, and acceptance throughout the illness journey were prominent in the participants' narratives. Receiving sufficient information and initiating treatment were important in negotiation of control. The results highlighted what facilitates and hinders adaptive coping. Aspects which facilitated positive coping were as follows: trust in clinician, feeling in control, feeling grateful, or accepting. Participants on a 'watch and wait' approach, while feeling appreciative, perceived the lack of treatment as difficult and frustrating. Implications for patient–clinician communication are discussed, particularly for patients on a 'watch and wait' who might need additional support in adjusting.